PERLINDUNGAN HUKUM PEMBELI HAK ATAS TANAH BERDASARKAN PERJANJIAN PENGIKATAN JUAL BELI SECARA BERTINGKAT OLEH NOTARIS MENURUT PRINSIP-PRINSIP EKONOMI SYARIAH - saprutro, troy permata; tohari, chamim (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
The agreement of a transaction is a prelimenary agreement before the main agreement (AJB) done in front of the PPAT. PPJB often causes a problem when the right of the land is treated as a commodity by the seller and it is not registered its changes in Agrarian Office. The registration may be done after the right of the land is changed into the lastest buyer.The approach of this research uses the approach of laws and the conceptual approach. The result of the analysis is concluded as the law protection of the latest buyer in accord with Government Regulations No. 24 of 1997 about the land registration, so that the Notary in maing PPJB has an obligation to pay attention to the principles of caution and the risks because of law concerning the document of the buyer.Key words : Agreement of transaction; document of transaction; the right of the land and the building.